Profit Persistence in the U.S. Audit Market - CICONTE, WILLIAM A.; KITTO, ANDREW R. (Journal of Accounting Research, 2026)
ABSTRACT This study investigates the relation between audit competition, audit quality, and auditor labor hours. Using proprietary data on auditor realization rates, we construct new measures of competition based on theory predicting that abnormal profits will quickly disappear when competition is high but persist over multiple periods when competition is low. We find consistent evidence of persistent abnormal profits among U.S. Big 4 engagements and that individual offices earn persistent abnormal returns, suggesting that the market is not perfectly competitive. Examining the consequences of lower competition, we find that profit persistence is negatively related to audit hours and positively related to audit quality. Although we are cautious about inferring causality, our findings suggest that lower competition is associated with more efficient and effective audits.